Effect of PEG Molecular Weight on the TiO2 Particle Structure and TiO2 Thin Films Properties - Mohd Rosli, ZULKIFLI; Zainab , Mahamud; Jeefferie, Abd Razak; masrom, kadir (2012)
This research, deals with modification of sol gel process for the synthesis of porous TiO2- PEG thin films with good structural integrity for environmental self-cleaning applications. Relatively, by adding the PEG with various molecular weights (300, 400, and 600) could influence the formation of TiO2 films structure and adhesion. Moreover, the formation of porous TiO2 associated with larger pores will accelerate the mass transfer of the treated contaminants in the larger pore channels. The advantages of the unique structures of as-prepared TiO2₂ films in the application of environmental self-cleaning systems are extensively studied by characterizing the produced films using various advanced characterization tools. Adhesion of TiO2 thin films become smooth and better surface with increasing the coating layers. The X-ray Diffraction spectrum of prepared coating shows present of anatase phase as major phase